Experimental evaluation of the flat wagon stability factor in operation conditions (Transport systems and technologies, 2019)
Ensuring traffic safety is one of the most important requirements for the operation of railways. Among accidents and disasters in railway transport the greatest danger is the derailment, as it can lead to grave consequences. The reasons of the derailment of wagons are due to malfunctions of rolling stock, deviations from the rules of the maintenance of the track, unsatisfactory dynamics of the train as well as the conditions of their operation. These failures, in particular, related to the destruction of the elements of the chassis, directly lead to the derailment of wagons. A significant drawback of the work of the railway transport of Ukraine is the restriction of the speed of trains with empty freight cars, which are equipped with models of wagons 18-100. Among the reasons for the derailments of the wheels of rail cars associated with malfunctions of the running gear, the following can be called: breakage of side frames and overhead bolts of trolleys, fracture of axles and wheels, malfunctions of roller bearings of the boot knot, wear of elements of friction oscillators and oscillation knobs on the superstructure beams, unacceptable variations in the size of the trolleys. Another important reason is the negative reduction of the wagon's packaging by more than 10% of the factory installed by the manufacturer.
Keywords: light-weight freight cars, running dynamic tests, speed, stability factor, derailments, fault, dynamics, computer simulation